Attitudes, beliefs, and behaviour to the adductor strengthening programme in male professional football: successfully adopted, but usually modified - Stensø, J.; Andersen, T. E.; Harøy, J. (British Journal of Sports Medicine, 2021)
Background The Adductor Strengthening Programme (ASP) is the first groin specific prevention programme proven to reduce the risk of groin problems in male football. Widespread dissemination of the programme and its preventative effect is recommended, however, successful implementation require researchers acquiring comprehensive knowledge of the implementation context. Using the Reach Effectiveness Adoption Implementation Maintenance (RE-AIM) framework is recommended for this procedure.